DYNAMIC ASSESSMENT OF INTERNAL WATERS OF THE JIZZAKH REGION - Kholmurzaev Jumanazar Ergashevich (Web of Journals Publishing, 2025)
In this article, the role of the law of periodicity on the basis of the natural geographic conditions of Jizzakh region, interconnectedness and interconnectedness of geological and geographical features is indicated.
Keywords: Natural geography and periodicity legalities, natural geographic processes, self-sufficiency, Water Resources, geographic factors, territorial, periodicity, rhythmic, cyclic, climatic, geomorphological structures.